Giving Voice to the Invisible Through the Use of Participatory Videos to Communicate Community-level Vulnerability to Pelagic Sargassum Influxes in the Eastern Caribbean - Bethia Thomas; Janice Cumberbatch (Journal of Participatory Research Methods)
The islands of the eastern Caribbean have been experiencing unprecedented pelagic sargassum influx events for over a decade now, which has become a significant concern for the region. Several studies have been conducted on this phenomenon, highlighting the need for diverse management responses to address this issue. However, most countries, including Saint Lucia, have been primarily reactive in their approach towards managing sargassum strandings. They have failed to implement a structured and organised plan to manage the influxes of sargassum, resulting in an ad hoc and unplanned response (Brooks et al. 2018, CRFM 2019, Djakourè et al. 2017, Doyle and Franks 2015, Gower and King 2011, Hinds et al. 2016, Hu et al. 2016, Oxenford et al. 2016, Wang and Hu 2017).